COMMUNITY PARTICIPATION IN THE FORMATION OF REGIONAL REGULATIONS IN BANGKALAN REGENCY IN THE FIELD OF TOURISM BASED ON SUSTAINABLE TOURISM - Laila, Novi Eka Syarifatul; Zaman, Nurus (Faculty of Law Universitas Trunojoyo Madura, 2023)
The legal basis for community participation is regulated in chapter XI of Law Number 12 of 2011 article 96 which states that the community has the right to provide input orally/in writing in the formation of laws and regulations. The problems studied in this research are: First, how is participation the people of Bangkalan Regency in planning, compiling and discussing local regulations on halal tourism. Second, what are the legal consequences if the formation of regional regulations in the field of tourism does not involve the participation of the community. The methodology used in this research is empirical juridical research with a normative/socio legal approach. The results obtained in this study are: First, how is the participation of the people of Bangkalan Regency in the process of forming regional regulations which are considered not fully in accordance with the provisions of Law Number 12 of 2011. Second, there are no rules regarding sanctions related to non-participation community participation in the process of forming local regulations/legislation. This is because the local government has not maximized the use of third party services in the process of forming local regulations in the preparation of academic papers and/or regional regulations.